Duplication of a Type-P5B-ATPase in Laverania and Avian Malaria Parasites and Implications About the Evolution of Plasmodium - Mark F. Wiser (Parasitologia)
Two related P-type ATPases, designated as ATPase1 and ATPase3, were identified in Plasmodium falciparum. These two ATPases exhibit very similar gene and protein structures and are most similar to P5B-ATPases. There are some differences in the predicted substrate-binding sites of ATPase1 and ATPase3 that suggest different functions for these two ATPases. Orthologues of ATPase3 were identified in all Plasmodium species, including the related Hepatocystis and Haemoproteus. ATPase3 orthologues could also be identified in all apicomplexan species, but no clear orthologues were identified outside of the Apicomplexa. In contrast, ATPase1 orthologues were only found in the Laverania, avian Plasmodium species, and Haemoproteus. ATPase1 likely arose from a duplication of the ATPase3 gene early in the evolution of malaria parasites. These results support a model in which early malaria parasites split into two clades. One clade consists of mammalian malaria parasites and Hepatocystis but excludes P. falciparum and related Laverania. The other clade includes Haemoproteus, avian Plasmodium species, and Laverania. This contrasts to recent models that suggest all mammalian malaria parasites form a monophyletic group, and all avian malaria parasites form a separate monophyletic group. ATPase1 may be a useful taxonomic/phylogenetic character for the phylogeny of Haemosporidia.